OPTIMASI KETERSEDIAAN DAN KEBUTUHAN AIR IRIGASI DI DAERAH IRIGASI KETANDAN KABUPATEN KEDIRI MENGGUNAKAN PROGRAM LINIER - Erfan Ferdiansyah; Faradlillah Saves (LPPM Universitas Bina Bangsa, 2023)
Water is a very important component to support the needs of living things throughout the world. Deficiency or excess of water requires an appropriate and efficient handling of water allocation management, in an effort to ensure the availability of irrigation water, especially for agriculture. This research aims to analyze the existing irrigation water needs in the Ketandan irrigation area, then look for several alternatives to determine effective and efficient cropping patterns and planting schedules, as well as to maximize agricultural land so as to produce maximum profits. In addition, this study also calculates the need for irrigation water for each type of plant that is planned. The optimization method used in the calculations in this study is the linear method with the help of the QM for Windows 4 application. From the results of the calculations and discussion of the optimization of the help of the linear program, it can be seen that the existing water requirement in the Kebunan irrigation area is 17.79 l/s/ha, the pattern planting Palawija-Rice-Rice with early August I planting and yields for each type of plant planned in one season are alternative IV (Rice I: 3.47 l/s/ha), (Rice II: 8.64 l/s/ha), and (Palawija: 9.58 l/s/ha) is the result of the highest profit value of IDR 144,355,900,000 per year, with a planting area of 1,610 Ha